Probing Anti-inflammatory Properties Independent of NF-κB Through Conformational Constraint of Peptide-Based Interleukin-1 Receptor Biased Ligands - Geranurimi, Azade; Cheng, Colin W. H.; Quiniou, Christiane; Zhu, Tang; Hou, Xin; Rivera, José Carlos; St-Cyr, Daniel J.; Beauregard, Kim; Bernard-Gauthier, Vadim; Chemtob, Sylvain; Lubell, William D. (Frontiers in Chemistry, 2019)
Interleukin-1β (IL-1β) binds to the IL-1 receptor (IL-1R) and is a key cytokine mediator of inflammasome activation. IL-1β signaling leads to parturition in preterm birth (PTB) and contributes to retinal vaso-obliteration characteristic of oxygen-induced retinopathy (OIR) of the premature infant. Therapeutics targeting IL-1β and IL-1R are approved to treat rheumatoid arthritis; however, all are large proteins with clinical limitations including immunosuppression, due in part to inhibition of NF-κB signalling, which is required for immuno-vigilance and cytoprotection. The all-D-amino acid peptide 1 (101.10, H-D-Arg-D-Tyr-D-Thr-D-Val-D-Glu-D-Leu-D-Ala-NH2) is an allosteric IL-1R modulator which exhibits functional selectivity and conserves NF-κB signaling, while inhibiting other IL-1-activated pathways. Peptide 1 has proven effective in experimental models of PTB and OIR. Seeking understanding of the structural requirements for the activity and biased signaling of 1, a panel of twelve derivatives was synthesized employing the various stereochemical isomers of α-amino-γ-lactam (Agl) and α-amino-β-hydroxy-γ-lactam (Hgl) residues to constrain the D-Thr-D-Val dipeptide residue. Using circular dichroism spectroscopy, the peptide conformation in solution was observed to be contingent on Agl, Hgl and Val stereochemistry. Moreover, the lactam mimic structure and configuration influenced biased IL-1 signaling in an in vitro panel of cellular assays as well as in vivo activity in murine models of PTB and OIR. Remarkably, all Agl and Hgl analogs of peptide 1 did not inhibit NF-κB signalling but blocked other pathways, such as JNK and ROCK2 phosphorylation contingent on structure and configuration. Efficacy in preventing preterm labour correlated with capacity to block IL-1β-induced IL-1β synthesis. Furthermore, the importance of inhibition of JNK and ROCK2 phosphorylation for enhanced activity was highlighted for prevention of vaso-obliteration in the OIR model. Taken together, lactam mimic structure and stereochemistry strongly influenced conformation and biased signaling. Selective modulation of IL-1 signalling was proven to be particularly beneficial for curbing inflammation in models of preterm labour and retinopathy of prematurity. A class of biased ligands have been created with potential to serve as selective probes for studying IL-1 signalling in disease. Moreover, the small peptide mimic prototypes are promising leads in developing immunomodulatory therapies with easier administration and maintenance of beneficial effects of NF-κB signalling.